2021
DOI: 10.1016/j.clnu.2020.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Specific gut microbial, biological, and psychiatric profiling related to binge eating disorders: A cross-sectional study in obese patients

Abstract: Conclusions: Non-targeted omics approaches allow to select specific microbial genera and two plasma metabolites that characterize BED obese patients. Further studies are needed to confirm their potential role as drivers or biomarkers of binge eating disorder. Food4gut, clinicaltrial.gov:NCT03852069, https://clinicaltrials.gov/ct2/show/NCT03852069.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 80 publications
1
19
0
Order By: Relevance
“…Very recently, Leyrolle and colleagues have examined the biological and psychiatric profile of obese patients with and without binge eating disorders through non-targeted multi-omics approaches. The authors suggest the potential role of certain GM layouts (i.e., with enrichment of Bifidobacterium and Anaerostipes , and depletion of Akkermansia and Intestimonas ) and/or plasma metabolites (i.e., food contaminants and food derived-metabolites) as drivers or biomarkers of binge eating disorders [ 19 ]. However, to our knowledge, no other studies have examined the relationship between GM and FA and, in general, very little information is available on GM functionality in uncontrolled eating behavior and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Leyrolle and colleagues have examined the biological and psychiatric profile of obese patients with and without binge eating disorders through non-targeted multi-omics approaches. The authors suggest the potential role of certain GM layouts (i.e., with enrichment of Bifidobacterium and Anaerostipes , and depletion of Akkermansia and Intestimonas ) and/or plasma metabolites (i.e., food contaminants and food derived-metabolites) as drivers or biomarkers of binge eating disorders [ 19 ]. However, to our knowledge, no other studies have examined the relationship between GM and FA and, in general, very little information is available on GM functionality in uncontrolled eating behavior and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence demonstrates that A. muciniphila can effectively improve metabolic disorders and is therefore regarded as a promising “next generation of beneficial microorganisms” [ 76 ]. Our findings also indicated that the abundance of A. muciniphila is indeed associated with many diseases, metabolic diseases such as type 2 diabetes (T2D) [ 77 ], obesity [ 78 80 ], Binge eating disorder (BED) [ 81 ] and psoriasis [ 82 ], which indicates that microecological agents may become an important therapeutic approach in the future.…”
Section: Discussionmentioning
confidence: 80%
“…Anaerostipes is closely related to eating habits and inflammation in obese people, but the precise mechanism is unclear [ 103 , 111 ]. It is reported that by promoting propionate formation via inositol or phytate, anaerostipes may lower the risk of metabolic disorders [ 112 ].…”
Section: Discussionmentioning
confidence: 99%